Between Desire and Anxiety: Music Performances during The COVID-19 Period In West Sumatera - Asril Asril; Adjuoktoza Rovylendes (Universitas Negeri Medan, 2024)
This article discusses the desire and anxiety of mutual attraction experienced by traditional and popular artists in West Sumatra during the COVID-19 pandemic. Musicians in tradition and entertainment who rely on the survival of music performance services are under heavy pressure by the COVID-19 pandemic situation because performances are rarely performed, even banned. Musicians committed to the creative field of creation experience the same thing. Live music performances are considered to be the cause of the gathering of many people, which results in being vulnerable to the transmission of the COVID-19 virus. However, they still channel the desire to perform live with the risk of getting in the way. Some are creative, using digital internet technology and social media to perform virtually. The research method used in collecting data is a mixture of field and virtual research. The tug-of-war between desire and anxiety is realized through live and virtual performances with non-maximal results. Music performances in the context of traditional music, composition, festivals, and entertainment during the COVID-19 period in West Sumatra are in the range between hope and fear in an incomparable dynamic of balance; they tend to be afraid rather than do it. Anxiety still haunts activists and event managers of musical performances.